The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1007/s00439-015-1571-4
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of ATF6 causes autosomal recessive achromatopsia

Abstract: Achromatopsia (ACHM) is an early-onset retinal dystrophy characterized by photophobia, nystagmus, color blindness and severely reduced visual acuity. Currently mutations in five genes CNGA3, CNGB3, GNAT2, PDE6C and PDE6H have been implicated in ACHM. We performed homozygosity mapping and linkage analysis in a consanguineous Pakistani ACHM family and mapped the locus to a 15.12-Mb region on chromosome 1q23.1–q24.3 with a maximum LOD score of 3.6. A DNA sample from an affected family member underwent exome seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 45 publications
2
55
0
1
Order By: Relevance
“…This intriguing result needs further investigation because if TUDCA prevents accumulation of misfolded proteins, it would not be expected to activate ATF6α. It was demonstrated recently that hypomorphic mutations in ATF6α in humans cause a rare syndrome, achromatopsia, that is associated with age-onset color blindness and loss of cone photoreceptors in the retina (Ansar et al 2015;Kohl et al 2015;Chiang et al 2017). Intriguingly, ATF6α deletion did not affect the function of rod photoreceptors, indicating a very selective requirement for ATF6α in cone photoreceptors.…”
Section: Atf6αmentioning
confidence: 99%
“…This intriguing result needs further investigation because if TUDCA prevents accumulation of misfolded proteins, it would not be expected to activate ATF6α. It was demonstrated recently that hypomorphic mutations in ATF6α in humans cause a rare syndrome, achromatopsia, that is associated with age-onset color blindness and loss of cone photoreceptors in the retina (Ansar et al 2015;Kohl et al 2015;Chiang et al 2017). Intriguingly, ATF6α deletion did not affect the function of rod photoreceptors, indicating a very selective requirement for ATF6α in cone photoreceptors.…”
Section: Atf6αmentioning
confidence: 99%
“…Recent human genetic evidence has begun to answer this question. Numerous mutations in ATF6α have now been identified in humans presenting with the developmental eye disorder achromatopsia, where alterations in ATF6 activity lead to impaired retinal development [6264]. Interestingly, these mutations differentially influence ATF6 activity.…”
Section: Therapeutic Targeting Of Upr Signaling Pathways To Amelioratmentioning
confidence: 99%
“…Using next-generation whole-exome sequencing, we recently discovered autosomal recessive mutations in the activating transcription factor 6 (ATF6) gene in patients with achromatopsia (1). ATF6 mutations span the entire coding region and include missense, nonsense, splice site, and single-nucleotide deletion and duplication changes (1)(2)(3). We previously showed that a missense mutation that introduced an arginine-to-cysteine substitution at amino acid residue 324 of the ATF6 protein compromised ATF6 activity in patient fibroblasts obtained from an achromatopsia family (1).…”
mentioning
confidence: 99%